Fornication as a criminal conduct in the Criminal Code Draft: Legal Protection versus Criminalization against Women - Laili Nur Anisah (Jurnal Perempuan, 2018)
On 14 February 2018 the Draft of the Criminal Code (RKUHP) was adjourned until an undetermined time, several articles deemed to be problematic. One of them is a criminal act of fornication. A new article will convict a denial-men who promises woman he has intercoursed with. Eventhough that article is meant to protect women, on the other hand, it can also be a factor to victimize women as perpetrator. This paper examines the position of women among the articles which will protect women's rights as well as those which criminalize them. This paper is a normative juridical study by using literature review and aims to find the problem and also intend solving it. The result, victimized-women protection Article in RKUHP should carefully be formulated in order not to allow victim women to be criminalized.